PENGARUH LEARNING MOTIVATION DAN PEER ASSISTED LEARNING TERHADAP STUDY ACHIEVEMENT PADA MAHASISWA PESERTA PROGRAM BEASISWA LPMAK DI PERGURUAN TINGGI - KOMANGAL, TEPY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Education has important roles in order to increase the human resources quality and to create the Indonesian aspirations to incarnate the wealth, to educate this nation. Every student in their education do their best in order to achieve their achievement. This study has aimed to investigate the influence of learning motivation and peer assisted learning toward students achievement of LPMAK (LembagaPengembanganMasyarakatAmungmedanKamoro) Scholarship Program in university which re consists of 100 respondents.The multiple linear regression analysis is used in this study and it showed that peer assisted learning and learning motivation positively significant toward study achievement in university students. Therefore, LPMAK is suggested not provide the scholarship only however the companion program which are by forming learning groups and evaluating the result, being a motivator to provoke the learning enthusiasm to gain the desired results.